Assessing catastrophic thinking associated with debilitating mental health conditions. Issue 3 (30th January 2018) - Moore, Emily; Adams, Heather; Ellis, Tamra; Thibault, Pascal; Sullivan, Michael J. L.
Abstract: Purpose: The present study examined the psychometric properties of the Symptom Catastrophizing Scale (SCS). The SCS items were drawn from the Pain Catastrophizing Scale but were modified to make them better suited to the context of debilitating mental health conditions that are not necessarily associated with pain. The number of items was reduced from 13 to 7, and the response scale was simplified. Methods: The SCS was administered to individuals diagnosed with Major Depressive Disorder (MDD) ( N = 79) or with a chronic musculoskeletal (MSK) condition ( N = 88). Results: Exploratory factor analyzes revealed single factor solutions of the SCS for both the MSK and MDD samples. The internal consistency of the SCS was good. The SCS was significantly correlated with measures of pain severity, depressive symptom severity and disability in both samples. Individuals with MDD scored higher on the SCS than individuals with MSK. The SCS was shown to be sensitive to treatment-related reductions in catastrophic thinking. Conclusions: Preliminary analyzes suggest that the SCS is a reliable and valid measure of symptom-related catastrophic thinking associated with debilitating mental health conditions. Implications for Rehabilitation: Although catastrophic thinking has been identified as a risk factor for disability, current assessment tools are not well suited for individuals with debilitating mental health conditions. This paper describes a brief assessment instrument that can be used to assess catastrophic thinking in individuals with debilitating mental health conditions. The results of this study suggest that targeting catastrophic thinking might yield reductions in symptom severity and disability in work-disabled individuals with major depressive disorder.